RESEARCH ON THE INFLUENCE OF WINE YEAST STRAINS ON THE FORMATION OF THE QUALITY OF HONEY FERMENTED BEVERAGES OF THE “PET-NAT” TYPE - Білько, Марина; Поліщук, Артем (SWorldJournal, 2025)
The work considers the technology of honey fermented beverages of the Pet-nat type in the direction of studying the influence of wine yeast strains on the completeness of honey must fermentation under conditions of low temperatures, elevated pressure and